PRMT5 Inhibitor EPZ015666 Decreases the Viability and Encystment of Entamoeba invadens - Rigoberto Ortiz-Hernández; Elmer Joel Millán-Casarrubias; Jeni Bolaños; Susana Munguía-Robledo; Carlos Vázquez-Calzada; Elisa Azuara-Licéaga; Jesús Valdés; Mario Alberto Rodríguez (Molecules)
Protein arginine methyltransferase 5 (PRMT5) is an enzyme that produces monomethyl arginine (MMA) and symmetric dimethyl arginine (sDMA), post-translational modifications that regulate several cellular processes, including stage conversion in parasitic protozoans. Entamoeba histolytica, the etiologic agent of human amebiasis, has two stages in its life cycle, the trophozoite, which is the replicative form, and the cyst, corresponding to the infective phase. The study of the molecular mechanisms that regulate differentiation in this parasite has been overdue because of a lack of efficient protocols for in vitro encystment. For this reason, Entamoeba invadens, a parasite of reptiles, has been used as a differentiation model system for the genus. Here, we demonstrated the presence of sDMA in E. invadens, which increases during encystment, and identified the PRMT5 of this microorganism (EiPRMT5). In addition, we performed 3D modeling of this enzyme, as well as its molecular docking with the PRMT5 inhibitor EPZ015666, which predicted the affinity of the drug for the active site of the enzyme. In agreement with these findings, EPZ015666 reduced trophozoite viability and encystment. Therefore, EiPRMT5 is a potential target for inhibiting the spread of amebiasis.